A Rigorous Approach to Large-Scale Elicitation and Analysis of Patient Narratives. (October 2020) - Schlesinger, Mark; Grob, Rachel; Shaller, Dale; Martino, Steven C.; Parker, Andrew M.; Rybowski, Lise; Finucane, Melissa L.; Cerully, Jennifer L.
Patient narratives have emerged as promising vehicles for making health care more responsive by helping clinicians to better understand their patients' expectations, perceptions, or concerns and encouraging consumers to engage with information about quality. A growing number of websites incorporate patients' comments. But existing comments have fragmentary content, fail to represent less vocal patients, and can be manipulated to "manage" providers' reputations. In this article, we offer the first empirical test of the proposition that patient narratives can be elicited rigorously and reliably using a five-question protocol that can be incorporated into large-scale patient experience surveys. We tested whether elicited narratives about outpatient care are complete (report all facets of patient experience), balanced (convey an accurate mix of positive and negative events), meaningful (have a coherent storyline), and representative (draw fulsome narratives from all relevant subsets of patients). The tested protocol is strong on balance and representativeness, more mixed on completeness and meaningfulness.